Immunohistochemical somatostatin receptor expression in insulinomas - Peltola Elina; Vesterinen Tiina; Leijon Helena; Hannula Päivi; Huhtala Heini; Mäkinen Markus; Nieminen Lasse; Pirinen Elina; Rönty Mikko; Söderström Mirva; Arola Johanna; Jaatinen Pia (John Wiley and Sons Inc, 2025)
Insulinomas are rare pancreatic neuroendocrine tumours. Most patients can be cured with surgery, but patients with a metastatic disease show impaired survival. The aim of this study was to evaluate somatostatin receptor (SSTR) 1-5 expression in insulinomas and to correlate the expression profile with clinicopathological variables and with patient outcome. This retrospective study involved 52 insulinoma patients. After histological re-evaluation, formalin-fixed paraffin-embedded tissue samples were processed into tissue microarrays and stained immunohistochemically with monoclonal SSTR1-5 antibodies. All the 52 tumours (49 non-metastatic, 3 metastatic) expressed at least one SSTR subtype. SSTR2 was expressed most frequently (71%), followed by SSTR3 (33%), SSTR1 (27%), SSTR5 (6%) and SSTR4 (0%). SSTR3 expression was associated with a larger tumour size (median diameter 19 mm vs. 13 mm, p = 0.043), and SSTR3 and SSTR5 expression were associated with impaired overall survival [HR 3.532 (95% CI 1.106–11,277), p = 0.033, and HR 6.805 (95% CI 1.364–33.955), p = 0.019 respectively]. Most insulinomas express SSTR2, which may be utilized in diagnostic imaging, and in planning individualized treatment strategies for insulinoma patients. Further studies are needed to clarify the association between SSTR profile and overall survival.